Taenia solium cysticercosis in West Africa: status update - (:unkn) unknown (My University, 2018)
Cysticercosis is caused by the larvae of the cestode Taenia solium. Few data are available on the prevalence of this disease in pigs and humans in West African countries. The aim of this study was to provide an overview of existing data concerning the spread of this parasitosis in the countries of the Economic Community of West African States (ECOWAS) on the basis of the literature published over the last five decades. Systematic searches for publications were carried out on PubMed and Google Scholar, as well as in certain regional and local journals. From a total of 501 articles initially retrieved concerning T. solium cysticercosis in West African countries, only 120 articles were relevant for this review and therefore finally retained. For pigs, only eight out of sixteen countries of the region have reported porcine cysticercosis. Post-mortem examination of carcasses at slaughterhouses, meat inspection at butcheries or tongue inspection in herds have been the main source of data, but may not entirely reflect actual parasite distribution. For humans, only five out of sixteen countries reported epidemiological data on neurocysticercosis. Most data referred to neurocysticercosis prevalence among epileptic patients or isolated clinical cases. Furthermore, existing data are often old. Overall, T. solium cysticercosis remains largely neglected in West Africa, and its prevalence appears not to be affected by any religion in particular. There is an urgent need to promote and implement health partnerships and programs on this disease in order to collect more data and identify sensitive populations in the countries of the ECOWAS area.
Keywords: African Research